(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the pathogenicity of the entomopathogenic fungus Metarhizium anisopliae on leaf-cutting ants Atta sexdens rubropilosa, under laboratory conditions. It was inoculated suspensions containing different concentrations of conidia on specimens of soldiers and workers, kept under controlled conditions. The mortality was verified daily until 15 days after inoculation. The experimental delineation was entirely random. Sporulation data were submitted to variance analysis and the average of the treatments were compared to each other by the Scott-Knott test. Probit analysis was performed to obtain the values of LT50 (in days). All isolates were pathogenic to A. sexdens rubropilosa, being more virulent for workers than for soldiers. Isolates IBCB 348, IBCB 410 and IBCB 425 were the most efficient in the mortality of the ants. Isolates IBCB 425 and UFGD 03 caused high percentages of confirmed mortality. The results showed that the tested isolates have the potential for using them as control agents of A. sexdens rubropilosa.